Indirect Comparison Between Bimekizumab and Brodalumab for the Management of Moderate to Severe Psoriasis: A 36-Week Real-Life Study - Luca Potestio; Fabrizio Martora; Flavia Raia; Gioacchino Lucagnano; Claudio Brescia; Ginevra Torta; Matteo Megna (Dermatology and Therapy)
Abstract Introduction Bimekizumab and brodalumab are characterized by a different mechanism of action if compared to the other anti-interleukin (IL)-17s which target IL-17A. Indeed, brodalumab acts on IL-17RA whereas bimekizumab acts on IL-17A, IL-17F, and IL-17AF cytokines. Currently, despite real-life data on the efficacy and safety of bimekizumab and brodalumab have been reported, data comparing these two drugs are absent. However, these data are mandatory to evaluate whether a different target of the same IL can be correlated with a different profile in terms of effectiveness and safety. Moreover, it should be underlined that bimekizumab and brodalumab stood out as the psoriasis treatments with the fastest onset of action, delivering quicker therapeutic responses compared to other drugs acting on IL-17. Methods A monocentric retrospective study was carried out enrolling patients affected by moderate to severe psoriasis undergoing treatment with brodalumab or bimekizumab. At baseline, clinical demographic details were collected. Clinical improvement [Psoriasis Area Severity Index (PASI), body surface area (BSA)] was collected at weeks 4, 16, and 36. Safety data were analyzed at the same timepoints. Results A total of 125 patients were enrolled in the study [bimekizumab: 53 (42.40%); brodalumab: 72 (57.6%)]. Psoriasis severity at baseline was similar between the two cohorts. Both PASI and BSA significantly reduced at each follow-up for both treatment cohorts. The bimekizumab group reached a higher percentage of PASI90/PASI100 response at each timepoint as compared to the brodalumab cohort. In particular, the percentage of PASI100 response was significantly higher in the bimekizumab group as compared to the brodalumab cohort at week 4 (41.5% vs 23.6%, p < 0.05) and at week 16 (67.9% vs 48.6%). Discontinuation for ineffectiveness was higher in the brodalumab cohort (8.3%) as compared to the bimekizumab group (3.8%), without statistical significance. As regards safety, two cases of eczematous reactions (bimekizumab: 2, brodalumab: 0), and five cases of candidiasis (bimekizumab: 4, brodalumab: 1) were collected. Overall, 3 (5.7%) and 1 (1.4%) patients discontinued bimekizumab and brodalumab because of adverse events, respectively. Conclusion Our study confirmed the efficacy and safety of both bimekizumab and brodalumab, up to 36 weeks of treatment. Although both drugs showed a significant improvement of the investigated scores from week 4, some differences in terms of PASI90 and PASI100 responses (higher for bimekizumab at each follow-up, with only PASI100 response significantly higher at week 4 and 16) were registered. No statistical significance was found for safety data and treatment failure.